2002
DOI: 10.1007/s00414-002-0334-7
|View full text |Cite
|
Sign up to set email alerts
|

Forensic significance of conduction system abnormalities as a precise cause of accidental death

Abstract: We examined the pathology findings of the cardiac conduction system in 42 human autopsies who were considered to have died an accidental death. Abnormalities in serial sections of the conduction system were found in seven and of these three had an accessory pathway in the conduction system. In one of these there was mild Ebstein's anomaly (ME), two had fibromuscular dysplasia of the atrioventricular node artery with mitral valve prolapse, and two others had abnormal routes showing fragmentation of the bundle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In our case, however, no cardiotonics were used during hospitalization. Moreover, we could not detect any findings which may have induced the arrhythmia, such as a small infarction scar, valvular disorder, hypertropic cardiomyopathy, or any other conductive system abnormalities (Nishida et al, 2002(Nishida et al, , 2003a(Nishida et al, , 2003b. Thus, it was considered that the pointer occurring to ventricular fibrillation was either the posterior wall of the bilateral ventricles or the AV conduction system from the AV node to the His' bundle.…”
Section: Discussionmentioning
confidence: 91%
“…In our case, however, no cardiotonics were used during hospitalization. Moreover, we could not detect any findings which may have induced the arrhythmia, such as a small infarction scar, valvular disorder, hypertropic cardiomyopathy, or any other conductive system abnormalities (Nishida et al, 2002(Nishida et al, , 2003a(Nishida et al, , 2003b. Thus, it was considered that the pointer occurring to ventricular fibrillation was either the posterior wall of the bilateral ventricles or the AV conduction system from the AV node to the His' bundle.…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, microscopic examination of the heart showed severe arteriolosclerosis and diffuse eosinophilic change of the cardiomyocytes, which is considered to be compatible with ischaemic heart disease. Nishida et al (2002) reported that the death of an individual could result from arrhythmia induced by abnormalities of the conduction system in forensic autopsy cases of accidental death. In the current case, stenosis of the lumen in both SA node and AV node arteries and lymphocyte infiltration in the bundle of His were observed in the conduction system, and these may have led to fatal arrhythmia.…”
Section: Discussionmentioning
confidence: 99%